2004
DOI: 10.1111/j.1349-7006.2004.tb03226.x
|View full text |Cite
|
Sign up to set email alerts
|

Targeted gene delivery using humanized single‐chain antibody with negatively charged oligopeptide tail

Abstract: e have been developing a non-viral cell-specific gene delivery system named immunoporter, using a modified monoclonal antibody.1-6) The original immunoporter was a conjugate between a monoclonal antibody and a cationic peptide poly-L-lysine (pLys).1) The Fab fragment of antibody was also conjugated with pLys.3) These whole-antibody or Fab-fragment immunoporters readily bound to DNA and the resulting complex, named an immunogene, delivered a reporter gene or therapeutic gene(s) to target cells in vitro and in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The properties of PTD-linked intrabody genes need to be examined in detail. In another promising approach, specific targeting of the therapeutic herpes simplex virus thymidine kinase gene was achieved with a so-called immunoporter consisting of a Fab fragment against EGF receptor conjugated with a cationic polylysine chain [106]. It was shown that the Fab immunore-porter carrying the herpes TK gene was effective in preventing the growth of EGF receptor-overexpressing tumour cells.…”
Section: Intrabody Gene Deliverymentioning
confidence: 99%
“…The properties of PTD-linked intrabody genes need to be examined in detail. In another promising approach, specific targeting of the therapeutic herpes simplex virus thymidine kinase gene was achieved with a so-called immunoporter consisting of a Fab fragment against EGF receptor conjugated with a cationic polylysine chain [106]. It was shown that the Fab immunore-porter carrying the herpes TK gene was effective in preventing the growth of EGF receptor-overexpressing tumour cells.…”
Section: Intrabody Gene Deliverymentioning
confidence: 99%